Biological Role of Gellan Gum in Improving Scaffold Drug Delivery, Cell Adhesion Properties for Tissue Engineering Applications - Muthukumar, Thangavelu (Molecules, 2019)
Over the past few decades, gellan gum (GG) has attracted substantial research interest in several fields including biomedical and clinical applications. The GG has highly versatile properties like easy bio-fabrication, tunable mechanical, cell adhesion, biocompatibility, biodegradability, drug delivery, and is easy to functionalize. These properties have put forth GG as a promising material in tissue engineering and regenerative medicine fields. Nevertheless, GG alone has poor mechanical strength, stability, and a high gelling temperature in physiological conditions. However, GG physiochemical properties can be enhanced by blending them with other polymers like chitosan, agar, sodium alginate, starch, cellulose, pullulan, polyvinyl chloride, xanthan gum, and other nanomaterials, like gold, silver, or composites. In this review article, we discuss the comprehensive overview and different strategies for the preparation of GG based biomaterial, hydrogels, and scaffolds for drug delivery, wound healing, antimicrobial activity, and cell adhesion. In addition, we have given special attention to tissue engineering applications of GG, which can be combined with another natural, synthetic polymers and nanoparticles, and other composites materials. Overall, this review article clearly presents a summary of the recent advances in research studies on GG for different biomedical applications.